Students’ Responses to the Application of Peer-Editing Group Correction for Cause–Effect Written Assignments - Ngasbun Egar; Siti Musarokah (Celt: A Journal of Culture, English Language Teaching & Literature, 2017)
The study aims at describing the students’ response to the application of Group Correction of Students’ Written Assignment technique assisted with Peer-Editing Worksheet in cause-effect essay teaching. The type of the study is descriptive qualitative research. The respondents of the study are the fourth semester students of the English Education Department of Universitas PGRI Semarang. The techniques used to collect the data are questionnaire and interview. The data are analyzed qualitatively The result of the study shows that through Group Correction of Students’ Written Assignment technique assisted with Peer-Editing Worksheet, the students can take some advantages. For example, the students can review other group’ works easily; they can also learn from other work errors to avoid making the same errors in their own writing, and add more ideas on their own writing by reading others’ works, etc. In conclusion, Group Correction of Students’ Written Assignment technique assisted with Peer-Editing Worksheet is useful learning technique for both the writer of the essay and the students who provide feedback.